APPLICATION OF MECHANICAL ADVANTAGE AND INSTANT CENTERS ON SINGULARITY ANALYSIS OF SINGLE-DOF PLANAR MECHANISMS - Zarkandi, Soheil (Journal of Mechanical Engineering, 2010)
Instantaneous kinematics of a mechanism becomes undetermined when it is in a singular configuration; this indeterminacy has undesirable effects on static and motional behavior of the mechanism. So these configurations must be found and avoided during the design, trajectory planning and control stages of the mechanism. This paper presents a new geometrical method to find singularities of single-dof planar mechanisms using the concepts of mechanical advantage and instant centers. Key Words: Planar mechanisms; Singularity; Instant center; Angular velocity; Mechanical advantage. DOI: 10.3329/jme.v41i1.5362 Journal of Mechanical Engineering, Vol. ME 41, No. 1, June 2010 50-57